A Bis(methylpiperazinylstyryl)phenanthroline as a Fluorescent Ligand for G‐Quadruplexes. Issue 17 (16th March 2016) - Wu, Shangrong; Wang, Linlin; Zhang, Nan; Liu, Ying; Zheng, Wei; Chang, Ang; Wang, Fuyi; Li, Songqin; Shangguan, Dihua
Abstract: G‐quadruplex (G4)‐forming sequences are prevalent in the genome and are considered to play important roles in gene regulation, and hence have been viewed as potential therapeutic targets in oncology. However, the structures and functions of most G4s in the genome are poorly understood. Therefore, the development of fluorescent probes and ligands for G4s is important for G4 research and drug discovery. Herein, we report a new G4 ligand, 2, 9‐bis[4‐(4‐methylpiperazin‐1‐yl)styryl]‐1, 10‐phenanthroline (BMSP), which was synthesized by a simple process. BMSP exhibits almost no fluorescence in aqueous buffer. The interaction of BMSP with G4s greatly enhances its fluorescence with a large Stokes' shift of 160 nm. Antiparallel human telomeric G4s exhibit the strongest binding affinity ( K d ≈0.13 μm ) to BMSP and induce a fluorescence enhancement of up to 150‐fold. BMSP binds to G4s through π–π stacking on the terminal G‐quartets. BMSP can enter live cells, and it strongly inhibits the growthof cancer cells rather than causing cell death. Our results suggest that BMSP has the potential to serve both as a fluorescent probe for some G4s and as a chemotherapeutic agent for cancer treatment. Abstract : New fluorescent probe : 2, 9‐Bis[4‐(4‐methylpiperazin‐1‐yl)styryl]‐1, 10‐phenanthroline (BMSP) has been designed and synthesized as a new fluorescent probe for DNA. It selectively binds to G‐quadruplexes through π–π stacking interactions (see graphic).